A Liquefaction Resistance of Sand-Fine Mixtures: Short Review with Current Research on Factors Influencing Liquefaction Resistance - Othman, Bakhtiar Affandy; Marto, Aminaton (International Journal of Integrated Engineering, 2019)
Sand is well understood as susceptible material to liquefy under seismic condition. In many cases of liquefaction, the loss of property and damages occurred due to the earthquake phenomenon are caused by sandy soils. Thus, many laboratory experiments and field tests on soil liquefaction engineering have been mandatorily focusing on the liquefaction resistance of sand-fine mixtures. The interaction between sand and fines particles appears to be well studied subject. However, there are some contradictory findings on some factors influencing liquefaction resistance in sand-fine mixtures. Therefore, this paper aim to present results and current findings from previous researchers which focused on sand-fine mixtures using various type of sand to interpret liquefaction resistance and its behaviour. In addition, microstructure test needs to be conducted for verification and analysis of the results on grading and particle sizes characteristics. It has been identified that recent findings on the particle size distribution and grading characteristics of sand in sand-fine mixtures are still contradicting. It has also been found that there are no study using different types of sand to reconstitute tropical sand-fine mixtures; and limited study focused on the coefficient uniformity, CU and coefficient of curvature, CC on liquefaction resistance relationship.